TRADITION OF MUTUAL ASSISTANCE IN RESEARCH BY FOREIGN SCIENTISTS (TAMADDUN NURI JURNALI, 2024)
The article analyzes the study of the tradition of mutual assistance from the point of view of foreign researchers. At the same time, the tradition of mutual assistance in the daily life of the Karakalpaks is mentioned.